Regarding some novel exponential travelling wave solutions to the Wu-Zhang system arising in nonlinear water wave model - Yel, G.; Baskonus, H. M.; Bulut, H. (Indian Assoc Cultivation Science, 2019)
In this paper, our main aim is to find the new travelling wave solutions to the Wu-Zhang system which describes dispersive long waves. Some new and important travelling wave solutions with rational and exponential function structures are successfully constructed by using the improved Bernoulli subequation function method. All the obtained solutions in this study satisfy the Wu-Zhang system. The interesting three- and two-dimensional surfaces to all the obtained solutions are plotted. We carried out all the computations and the graphics plots in this paper with aid of the Wolfram Mathematica 9.
Keywords: Wu-Zhang system; Dispersive long waves; Improved Bernoulli subequation function method; New travelling wave solutions